2011
DOI: 10.2903/j.efsa.2011.2313
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Flavouring Group Evaluation 13, Revision 2 (FGE.13Rev2): Furfuryl and furan derivatives with and without additional side-chain substituents and heteroatoms from chemical group 14

Abstract: The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids of the European Food Safety Authority was requested to evaluate 27 flavouring substances in the Flavouring Group Evaluation 13, Revision 2, using the Procedure in Commission Regulation (EC) No 1565/2000. Three of the substances [Fl‐no: 13.125, 13.155 and 13.162] were considered to have genotoxic potential. The remaining 24 substances were evaluated through a stepwise approach (the Procedure) that integrates information on structure‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…Nevertheless, the experimentally obtained genotoxicity data indicate that substance .054] may give rise to DNA damage, which may result in chromosomal aberrations rather than gene mutations. The formation of DNA-reactive metabolites may be anticipated (EFSA CEF Panel, 2011c). In combination with this, the available genotoxicity data are sufficiently strong to raise a concern, which would preclude the evaluation of the candidate substance in subgroup VI-B through the Procedure.…”
Section: Efsa Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the experimentally obtained genotoxicity data indicate that substance .054] may give rise to DNA damage, which may result in chromosomal aberrations rather than gene mutations. The formation of DNA-reactive metabolites may be anticipated (EFSA CEF Panel, 2011c). In combination with this, the available genotoxicity data are sufficiently strong to raise a concern, which would preclude the evaluation of the candidate substance in subgroup VI-B through the Procedure.…”
Section: Efsa Considerationsmentioning
confidence: 99%
“…The Panel noted further that for 7 of these 17 substances 13.052,13.054,13.059,13.061,13.069 and 13.083], use levels have not yet been submitted. Table 5: Genotoxicity (In Vivo) Evaluated by EFSA in FGE.13Rev2 (EFSA CEF Panel, 2011c) . 73 Table 6: The Union list of flavourings and source materials was established by Commission Implementing Regulation (EC) No 872/2012.…”
mentioning
confidence: 99%
“…These metabolites are all expected to be excreted in the urine. A more detailed discussion on the metabolism of sulphur compounds can be found in FGE.13Rev2 (EFSA CEF Panel, 2011b).…”
Section: Metabolism Of Substances In Subgroup A-imentioning
confidence: 99%
“…To a very small extent ring C-oxidation may be followed by ring cleavage to yield alpha-diketone and thioamide fragments. The acyl-substituted thiazoles 15.039,15.085 and 15.116] may also be expected to undergo keto-reduction, possibly followed by conjugation, similar to acyl derivatives of furanes (EFSA CEF Panel, 2011b) and pyrazines (EFSA CEF Panel, 2011a).…”
Section: A-subgroups (Substances With Aromatic Ring Structures)mentioning
confidence: 99%
“…The Panel concluded that all the substances in the JECFA flavouring group of sulfur-substituted furan derivatives are structurally related to a group of sulfur-containing furane derivatives evaluated within the group of 'Furfuryl and furan derivatives with and without additional side-chain substituents and heteroatoms from chemical group 14 evaluated by EFSA in the Flavouring Group Evaluation 13, Revision 2 (FGE.13Rev2; (EFSA CEF Panel, 2011).…”
Section: Efsa Considerationsmentioning
confidence: 99%